Climate change impact on tropical cyclone evolution and storm surge severity in the east coast of Peninsular Malaysia - Mohd Anuar, N. (Institute of Physics Publishing, 2020)
Analysing sound information and vast amount of reliable data on tides, waves and tropical cyclone genesis require tireless effort and a great deal of research time, in an ever changing climate conditions. Here, we investigate the strong monsoon wave height in the East Coast of Peninsular Malaysia using more than 20 years of hindcasted wave and tide level data collected at selected locations. A correlation analysis performed on maximum wave heights and surge levels indicated a weak strength of dependency but shown high occurrence during Northeast Monsoon period, concurred with previous storm surge data analysis. We use historical report of West-North Pacific tropical cyclone and global sea surface temperature information to elicit historic patterns of extreme storm tracks and passing distance to understand the trends over the collective years (1986-2012) and to project a concurrent events between the cyclone and surge data. The distance of passing cyclone in closer range does not gives the expected surge height in three out of five selected tide stations, but tropical cyclones in greater distance than 500 km seems to inject a high surge in the east coast. This paper provides a case study of effective cross-sector data analysis in a natural hazard context. Â© Published under licence by IOP Publishing Ltd.